Analisis Kebijakan Pengembangan Toba Caldera Geopark: Perspektif Kritis Terhadap Dampak Lingkungan dan Keadilan Sosial Bagi Masyarakat Adat - Qania Azmi; Fadillah Tasali; Inne Jeniarti; M. Joharis (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The development of the Toba Caldera Geopark as a national priority tourism destination is part of the government’s efforts to drive regional economic growth, improve community welfare, and strengthen Indonesia’s position in sustainable tourism. However, its implementation presents significant challenges in balancing economic development, environmental sustainability, and social justice, particularly for indigenous communities around the area. This study aims to analyze the impact of the Toba Caldera Geopark development policy on the environment and local indigenous communities. A multidisciplinary approach was employed, combining qualitative methods through in-depth interviews and participatory observations, along with quantitative data from surveys and official secondary sources. The results indicate potential conflicts between tourism infrastructure development and nature conservation, including environmental degradation and the erosion of local cultural values. Additionally, there is a risk of marginalization of indigenous communities in terms of access to natural resources and their involvement in decision-making processes. Therefore, this study recommends the need for more inclusive and sustainable policies that place indigenous communities at the center of geopark management. Active participation of local communities, recognition of customary land rights, and development approaches based on local wisdom are essential to achieving equitable, sustainable, and environmentally responsible development of the Toba Caldera Geopark.